2006
DOI: 10.1016/j.theriogenology.2006.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma improves cryopreservation of Iberian red deer epididymal sperm

Abstract: We tested the protective action of seminal plasma on epididymal spermatozoa from Iberian red deer, especially considering cryopreservation, as a means for germplasm banking improvement. We obtained seminal plasma by centrifuging electroejaculated semen, and part of it was thermically inactivated (denatured plasma; 55 degrees C 30 min). Epididymal samples (always at 5 degrees C) were obtained from genitalia harvested after regulated hunting, and pooled for each assay (five in total). We tested three seminal pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 59 publications
0
37
0
1
Order By: Relevance
“…Epididymal spermatozoa have been harvested from a variety of species like cats (Filliers et al, 2008;Hermansson & AxnÈr, 2007), dogs (Garcia-Macias et al, 2006;Hewitt et al, 2001;Nothling et al, 2007;Ponglowhapan et al, 2006), rats (Yamashiro et al, 2007), horses (Braun et al, 1994;Bruemmer, 2006;Heise et al, 2011;Johnson & Coutinho da Silva, 2008;Melo et al, 2008), cattle (Goovaerts et al, 2006;Martins, Rumpf, Pereira, & Dode, 2007), pigs (Ikeda et al, 2002), sheep (Garcia-Macias et al, 2006), goats (Blash, Melican, & Gavin, 2000), red deer (Fernandez-Santos et al, 2006;Garcia-Macias et al, 2006;MartÌnez-Pastor et al, 2006), Spanish Ibex , African buffalo (Herold et al, 2006), North American buffalo (Lessard at al., 2009) and monkeys (Goff et al, 2009;Ng et al, 2002). Pregnancies and offspring after AI with epididymal spermatozoa have been produced amongst others in horses (Barker & Gandier, 1957;Heise et al, 2010;Papa et al, 2008), dogs (Hori, Hagiuda, Kawakami, & Tsutsui, 2005) and Spanish Ibex (SantiagoMoreno et al, 2006).…”
Section: Use Of Epididymal Spermatozoa For Aimentioning
confidence: 99%
“…Epididymal spermatozoa have been harvested from a variety of species like cats (Filliers et al, 2008;Hermansson & AxnÈr, 2007), dogs (Garcia-Macias et al, 2006;Hewitt et al, 2001;Nothling et al, 2007;Ponglowhapan et al, 2006), rats (Yamashiro et al, 2007), horses (Braun et al, 1994;Bruemmer, 2006;Heise et al, 2011;Johnson & Coutinho da Silva, 2008;Melo et al, 2008), cattle (Goovaerts et al, 2006;Martins, Rumpf, Pereira, & Dode, 2007), pigs (Ikeda et al, 2002), sheep (Garcia-Macias et al, 2006), goats (Blash, Melican, & Gavin, 2000), red deer (Fernandez-Santos et al, 2006;Garcia-Macias et al, 2006;MartÌnez-Pastor et al, 2006), Spanish Ibex , African buffalo (Herold et al, 2006), North American buffalo (Lessard at al., 2009) and monkeys (Goff et al, 2009;Ng et al, 2002). Pregnancies and offspring after AI with epididymal spermatozoa have been produced amongst others in horses (Barker & Gandier, 1957;Heise et al, 2010;Papa et al, 2008), dogs (Hori, Hagiuda, Kawakami, & Tsutsui, 2005) and Spanish Ibex (SantiagoMoreno et al, 2006).…”
Section: Use Of Epididymal Spermatozoa For Aimentioning
confidence: 99%
“…A consequence of centrifugation is the removal of seminal plasma and their potential effects on semen quality. Although some studies in several species have shown the beneficial effects of seminal plasma addition on spermatozoa during processing and cryopreservation (deer: Martinez-Pastor et al 2006;ram: Ollero et al 1997), others have reported deleterious effects (dog: Rota et al 2006;goat: Pellicer-Rubio et al 1997;ram: Ritar and Salamon 1982;stallion: Carver and Ball 2002;Sieme et al 2004;bull: Way et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In other animal species, improvement in sperm qualities or fertility by SP has been frequently reported [3,4,6,7]. For example, in Iberian red deer [6], no difference due to the presence or absence of SP was noted in epididymal sperm motility before freezing, but motility was significantly higher when sperm were treated with SP after freezing-thawing. The same phenomenon has been reported [4,7] in dogs.…”
mentioning
confidence: 96%
“…However, no difference was noted in lectin binding between feline epididymal and ejaculated sperm. The effects of SP on sperm functions have been reported to be positive or negative in various animal species [3,4,[6][7][8]11].Kawakami et al[5] investigated protein attachment on the surfaces of canine caudal epididymal and ejaculated sperm. They observed that PHA-E lectin did not bind to caudal epididymal sperm but bound to ejaculated sperm and suggested that a PHA-E lectin-binding glycoprotein, N-acetyl-D-galactosamine, is a decapacitation factor.…”
mentioning
confidence: 99%
See 1 more Smart Citation